Ribosome profiling in archaea reveals leaderless translation, novel translational initiation sites, and ribosome pausing at single codon resolution. Issue 10 (8th May 2020) - Gelsinger, Diego Rivera; Dallon, Emma; Reddy, Rahul; Mohammad, Fuad; Buskirk, Allen R; DiRuggiero, Jocelyne
Abstract: High-throughput methods, such as ribosome profiling, have revealed the complexity of translation regulation in Bacteria and Eukarya with large-scale effects on cellular functions. In contrast, the translational landscape in Archaea remains mostly unexplored. Here, we developed ribosome profiling in a model archaeon, Haloferax volcanii, elucidating, for the first time, the translational landscape of a representative of the third domain of life. We determined the ribosome footprint of H. volcanii to be comparable in size to that of the Eukarya. We linked footprint lengths to initiating and elongating states of the ribosome on leadered transcripts, operons, and on leaderless transcripts, the latter representing 70% of H. volcanii transcriptome. We manipulated ribosome activity with translation inhibitors to reveal ribosome pausing at specific codons. Lastly, we found that the drug harringtonine arrested ribosomes at initiation sites in this archaeon. This drug treatment allowed us to confirm known translation initiation sites and also reveal putative novel initiation sites in intergenic regions and within genes. Ribosome profiling revealed an uncharacterized complexity of translation in this archaeon with bacteria-like, eukarya-like, and potentially novel translation mechanisms. These mechanisms are likely to be functionally essential and to contribute to an expanded proteome with regulatory roles in gene expression.